Manifestações patológicas em conjuntos habitacionais: a degradação da fachadas - Braga, Celia Cavalcanti (2010)
Cases of deterioration in building facades in Recife and surroundings have been subject to the attention of technical construction in the state of Pernambuco. The presence of visual changes caused by pathological manifestations (fungi, cracks, stains, etc.) in these areas is a warning sign that their performance is in decline. The word pathology, originating in medicine, is used in civil engineering, by analogy, to determine diseases that are installed in several parts of the building, especially the most exposed to natural degrading agents (wind, rain, etc.): the facade. This work presents a study case of pathological problems surveyed in the facades of all buildings type t3(ground floor + three more floors) in three social housing projects: Beira Rio, Casarão do Cordeiro and Abençoada por Deus, supported by the Prefeitura da Cidade do Recife (Recife City Hall). Some pathologies related to the use of paint over mortar rendering or over brick only, were observed on the four facades of these buildings. First of all, the Lichtenstein method(1986) was used to guide the early stages of the work because it organizes the different steps to be taken all during the study, which range from the collection of data from the places visited to the diagnosis, conduct and therapy to be adopted. However, this method was slightly adapted for this study. Secondly, two other methods were used to help with recording and counting the pathologies observed on the facades: the methods of incidence and intensity. One hundred and seventy two facades were inspected and a series of problems on the vertical surfaces of these buildings was recorded. The pathologies were as follows: fungus, cracks, blisters on paint, discoloration, stains from corrosion, efflorescence, stain on paint, peeling paintwork, crumbling brickwork, moisture staining in the brickwork. After presenting and discussing the results obtained by comparing the data, it was concluded that the origin of these pathologies arose from the architectural planning, the way it was implemented and the quality of the materials used to clad the walls.